1995
DOI: 10.1046/j.1365-313x.1995.7040613.x
|View full text |Cite
|
Sign up to set email alerts
|

The amylose content in rice endosperm is related to the post‐transcriptional regulation of the waxy gene

Abstract: SummaryThe waxy (Wx) gene of rice encodes a granule-bound starch synthase (GBSS = waxy protein} required for the synthesis of amylose in endosperm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
274
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(303 citation statements)
references
References 30 publications
15
274
0
1
Order By: Relevance
“…Judging from the amylose content of the isogenic lines, Kikuchi (1988) suggested that Koshihikari, the most popular japonica rice variety in Japan, also harbours the Wx-b gene. Recently, sequence analysis of the wx locus has revealed that the low level of expression of the Wx-b gene results from a single nucleotide substitution at the 5′ splice site of the first intron (Cai et al 1998, Hirano et al 1998, Isshiki et al 1998, Wang et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Judging from the amylose content of the isogenic lines, Kikuchi (1988) suggested that Koshihikari, the most popular japonica rice variety in Japan, also harbours the Wx-b gene. Recently, sequence analysis of the wx locus has revealed that the low level of expression of the Wx-b gene results from a single nucleotide substitution at the 5′ splice site of the first intron (Cai et al 1998, Hirano et al 1998, Isshiki et al 1998, Wang et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivars with different grain qualities are also required for medicinal, ceremonial, or special production purposes. Tremendous efforts have been made to understand the genetic basis of rice eating and cooking quality (ECQ) (1)(2)(3)(4)(5)(6), which is mainly affected by three physicochemical properties: amylose content (AC), gel consistency (GC), and gelatinization temperature (GT) (7)(8)(9), but so far only the Waxy gene (10) has been found to affect AC and ALK (4,11) to GT. We are therefore still facing many challenging questions.…”
mentioning
confidence: 99%
“…Glutinous rice contains a G-to-T mutation at the 59 splice site of Wx intron 1, which leads to incomplete post-transcriptional processing of the pre-mRNA (Wang et al 1995;Bligh et al 1998;Cai et al 1998;Hirano et al 1998;Isshiki et al 1998). Glutinous rice varieties do not have detectable levels of spliced mRNA as a result of this mutation (Wang et al 1995;Bligh et al 1998).…”
mentioning
confidence: 99%
“…Glutinous rice contains a G-to-T mutation at the 59 splice site of Wx intron 1, which leads to incomplete post-transcriptional processing of the pre-mRNA (Wang et al 1995;Bligh et al 1998;Cai et al 1998;Hirano et al 1998;Isshiki et al 1998). Glutinous rice varieties do not have detectable levels of spliced mRNA as a result of this mutation (Wang et al 1995;Bligh et al 1998). Interestingly, some degree of amylose synthesis is restored in cultivars that carry the mutation but display cryptic splice-site activation, which results in alternative Wx pre-mRNA splicing patterns (Wang et al 1995;Bligh et al 1998;Cai et al 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation